New Method for the Orthogonal Labeling and Purification of Toxoplasma gondii Proteins While Inside the Host Cell - Wier, Gregory M. (American Society of Microbiology, 2015)
Toxoplasma gondii is an obligate intracellular protozoan parasite that is capable of causing severe disease in immunocompromised humans. How T. gondii is able to modulate the host cell to support itself is still poorly understood. Knowledge pertaining to the host-parasite interaction could be bolstered by developing a system to specifically label parasite proteins while the parasite grows inside the host cell. For this purpose, we have created a strain of T. gondii that expresses a mutant Escherichia coli methionyl-tRNA synthetase (MetRSNLL) that allows methionine tRNA to be loaded with the azide-containing methionine analog azidonorleucine (Anl). Anl-containing proteins are susceptible to a copper-catalyzed “click” reaction to attach affinity tags for purification or fluorescent tags for visualization. The MetRSNLL-Anl system labels nascent T. gondii proteins in an orthogonal fashion, labeling proteins only in MetRSNLL-expressing parasites. This system should be useful for nonradioactive pulse-chase studies and purification of nascently translated proteins. Although this approach allows labeling of a diverse array of parasite proteins, secreted parasite proteins appear to be only minimally labeled in MetRSNLL-expressing T. gondii. The minimal labeling of secreted proteins is likely a consequence of the selective charging of the initiator tRNA (and not the elongator methionine tRNA) by the heterologously expressed bacterial MetRS.